SEG Technical Program Expanded Abstracts 2012 2012
DOI: 10.1190/segam2012-1106.1
|View full text |Cite
|
Sign up to set email alerts
|

Oil shale anisotropy measurement and sensitivity analysis

Abstract: We have measured velocity anisotropy on 13 core samples from an organic shale oil reservoir with differential pressure up to 3000 psi. The pressure effect on velocities is generally stronger in direction normal to the bedding than along the bedding, and thus the anisotropy decreases with increasing differential pressure. P-wave anisotropy and vertical Vp/Vs ratio have good correlation with TOC content: the higher is the TOC content, the stronger is Pwave anisotropy and the lower is Vp/Vs ratio. The measured P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…where VPθ is the phase velocity. As Yan, Han, and Yao () pointed out, this small angle error can have significant effect on estimation of c 13 and δ. In Fig.…”
Section: Uncertainty In Laboratory Velocity Anisotropy Measurementmentioning
confidence: 96%
“…where VPθ is the phase velocity. As Yan, Han, and Yao () pointed out, this small angle error can have significant effect on estimation of c 13 and δ. In Fig.…”
Section: Uncertainty In Laboratory Velocity Anisotropy Measurementmentioning
confidence: 96%
“…The angle error does not cause significant difference in the estimation of δ for this sample, but as shown by Yan et al (2012), a 5°angle error can cause greater error in c 13 and δ in some cases. V P90°i s not shifted because it is measured on the axial direction of the horizontal plug.…”
Section: A N G L E E R R O R D E T E C T I O Nmentioning
confidence: 62%
“…Yan, Han and Yao (2012) showed that 1% error in estimating of 45°P-wave phase velocity can cause significant error in estimating c 13 and δ. For this sample, the scalar difference between the 45°group velocity and the 45°phase velocity is about 6%.…”
Section: G R O U P V E L O C I T Y a N D P H A S E V E L O C I T Y M mentioning
confidence: 99%
See 2 more Smart Citations